The effects of natural compounds on immune cell activation. The effects of dietary fish oil on ex vivo chemokine secretion by murine splenocytes and lichen or cyanobacterial polysaccharides on in vitro cytokine secretion and signaling pathways in human monocytes - Guðný Ella Thorlacius 1984- (2011)
Various plants and natural products have been used in folk medicine for a long time and their popularity has grown steadily in recent years. Fish oil has been popular among the Icelandic nation and a number of studies have revealed numerous benefits of fish oil consumption for many inflammatory diseases that increasingly plague the Western world. Lichens are quite unique both in physiological structure and their production of secondary metabolites. A few of them have been used in Icelandic folk medicine for centuries. Studies have shown that many polysaccharides from plants and other life-forms can mediate various biological effects. Given the prevalence of numerous inflammatory diseases, products with immunomodulatory effects are an important research subject. One way to examine the effects of natural products on the immune system is to observe their effects on the innate immune responses of animals (in vivo/ex vivo)or to examine their effects directly on cells in vitro. The aim of this project was to assess the effects of dietary fish oil on murine splenocyte chemokine secretion ex vivo, as well as assessing the effects of polysaccharides from the lichens Cetraria islandica, Collema glebulentum and Collema flaccidum and the cyanobacteria Nostoc commune on the activation of human monocytes in vitro. Mice were fed a fish oil diet or control diet for six weeks and then euthanized and spleens collected. The spleens were passed through strainers to form a single cell suspension and seeded in 96 well plates with or without stimulation (lipopolysaccharide for monocytes/macrophages and antibodies against CD3 and CD28 for T cells) and cultured for 48 hours. The culture supernatants were collected and chemokine concentration measured using ELISA. Polysaccharides from the lichens or cyanobacteria were purified at the laboratories of Sesselja Ómarsdóttir and Elín Soffía Ólafsdóttir at the Faculty of Pharmaceutical Sciences at the University of Iceland. Human THP-1 monocytes were seeded in 48 well plates and pre-treated ...